La influencia de la formación del profesor en el diseño de un curso en línea = Teacher formation influence in online course design - McAnally-Salas, Lewis; Armijo de Vega, Carolina; Organista Sandoval, Javier (Educação)
Influence of pedagogical orientation, pedagogical knowledge and technological skills of a teacher over a on-line course design where analyzed. Surveys and interviews to identify pedagogical orientation, pedagogical knowledge and technological skills was used. After its conclusion the structure and coherence of online course design were evaluated, including from a constructivist learning environment perspective. It was found that the course design has a satisfactory degree of coherence between its components and corresponds to a contructivist learning environment, this results contrast with the teacher’s lack of pedagogical knowledge and technological skills